2012
DOI: 10.1073/pnas.1113793109
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-132 dysregulation in schizophrenia has implications for both neurodevelopment and adult brain function

Abstract: Schizophrenia is characterized by affective, cognitive, neuromorphological, and molecular abnormalities that may have a neurodevelopmental origin. MicroRNAs (miRNAs) are small noncoding RNA sequences critical to neurodevelopment and adult neuronal processes by coordinating the activity of multiple genes within biological networks. We examined the expression of 854 miRNAs in prefrontal cortical tissue from 100 control, schizophrenic, and bipolar subjects. The cyclic AMP-responsive element binding- and NMDA-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
203
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(214 citation statements)
references
References 45 publications
9
203
1
1
Order By: Relevance
“…It is of interest that SREB2 is the target of several microRNAs. One of these (miR-137) has been recently associated with schizophrenia in a large genome-wide association study (Ripke et al, 2011), while another (miR-876-3p) has been found to be overexpressed in the DLPFC of patients with bipolar disorder (Miller et al, 2012). In the same report, miR-17-5p expression was found to be dysregulated both in schizophrenia and in bipolar disorder; the evidence for this miRNA binding in the SREB2 locus, however, is weaker for this miRNA (http://www.targetscan.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest that SREB2 is the target of several microRNAs. One of these (miR-137) has been recently associated with schizophrenia in a large genome-wide association study (Ripke et al, 2011), while another (miR-876-3p) has been found to be overexpressed in the DLPFC of patients with bipolar disorder (Miller et al, 2012). In the same report, miR-17-5p expression was found to be dysregulated both in schizophrenia and in bipolar disorder; the evidence for this miRNA binding in the SREB2 locus, however, is weaker for this miRNA (http://www.targetscan.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a subset of BDNF gene promoters in schizophrenia prefrontal cortex cannot be fully accessed by the growth arrest and DNA-damage-inducible, beta GADD45b protein, which coordinates DNA demethylation pathways, resulting in excess DNA methylation and hydroxymethylation of BDNF promoter IX and decreased transcription from that site (Gavin et al, 2012). Likewise, dysregulated expression of DNA methyltransferase DNMT3a and various transcription factors was linked to decreased expression of the NMDA-sensitive small RNA, mIR-132 (Miller et al, 2012).…”
Section: Epigenetics and Transcriptional (Dys) Regulation In Diseasedmentioning
confidence: 99%
“…The expression of BDNF mRNA and protein is reduced in the dorsolateral prefrontal cortex (PFC) of subjects with schizophrenia (8); another study demonstrated a positive correlation between reduced BDNF mRNA levels and reduced spine density in the same subjects with schizophrenia (58). miR-132 expression is reduced in the PFC from subjects with schizophrenia and in the PFC of adult mice chronically treated during postnatal development with the noncompetitive NMDAR antagonist MK-801 (18). Further experiments will be needed to directly test whether the spine deficits in SR −/− mice are caused by abnormalities in BDNF or miR-132 expression.…”
Section: −/−mentioning
confidence: 99%
“…These noncoding RNAs regulate neural plasticity by controlling the translation of target mRNA transcripts. Expression of the neuron-enriched miR-132 is reduced in schizophrenia (18); it regulates basal and activityinduced neurite outgrowth (19), and is up-regulated in vivo in response to external stimuli (20,21). Importantly, both BDNF (22) and miR-132 (17) expression are increased by NMDAR receptor (NMDAR) activation.…”
mentioning
confidence: 99%